Entreprenörskap på landsbygden - Fagerson, Lisa; Skogh, Emilia (2011)
For a long time, economic activity has decreased and shows a downward trend in the food sector. To break this requires efforts to strengthen corporate position with the ability to meet market challenges. In the small producers is a great potential for them to be able to increase its profitability thanks to its ability to offer added value in the product. But to achieve this requires not only a willingness and creativity out of the ordinary but also factors that lead us into this report, current issues. The issues are related to marketing, brand building and the importance of developing a stable network. The study aims to investigate how small businesses operate in rural areas are experiencing the possibilities of support from various networks and organizations and that, from a business perspective, and also see which areas that they need more support in to achieve a growing business. The work has been followed by an inductive method, when we initially could not say anything about the empirical results. To answer the study questions have six entrepreneurs interviewed. A distinction has been made to only interview the small-scale entrepreneurs operating in rural areas within the Mälardalen region and is what we describe as small with 0-5 employees. The reason for the choice we made was to our own preferences when the case companies were within a reasonable distance and with our already underlying knowledge of the region's market position within the green sector. A literature study has been made where the angles, facts and theories emerging from the previous studies on the subject. After interviews with the entrepreneurs have the choice of theory identified and lays the groundwork for what is the work discussion and conclusions. The conclusion of this work demonstrates that common to all the participating companies is that the social network is of great importance and they are also satisfied with the networks to which they are currently part of which is controlled much of the individual. So therefore, no major actions in terms of networking, but the emphasis should instead be on marketing and brand building. Another conclusion that emerged with their work is that the gist of all the combined factors such as entrepreneurship, networking, marketing and brand building is the basis for its establishment and development. The size of the company is irrelevant; however, the company's growth depends on a strong-willed and energetic business owner in particular in the case, as in this study when the entrepreneur is the company.